Functional Outcome of Darrach procedure in the Treatment of Ulnar Impaction Syndrome (Journal of Pakistan Orthopaedic Association, 2013)
Objective: To determine the Functional Outcome of Darrach procedure in the treatment of ulnar impaction syndrome Materials and Methods: This Retrospective Cohort study was carried out at Department of Orthopaedics and Traumatology, Khyber Teaching Hospital, Peshawar during the period from August 2007 to August 2013 including 30 patients who underwent Darrach’s distal ulnar resection for ulnar impaction syndrome. We retrospectively reviewed the charts and radiographs of 30 patients who underwent Darrach procedure. Results: Over a 6-year-period, 22 women and 8 men with a mean age of 35years (range, 20 to 50 years) had resection of the distal part of the ulna (Darrach procedure) to address ulnar impaction syndrome. Thirty wrists were operated upon. At an average follow-up of 2 years, 80% patients were satisfied and 63.3% had returned to their job. Majority (70%) of the wrists were pain free. Functional outcome was good in half of the wrists. There was a mean improvement of 23 and 11 degrees in supination and ulnar deviation respectively. Complications noticed were wrist instability in two patients and radioulnar convergence and carpal tunnel syndrome each in one patient. Conclusion: Darrach procedure improves wrist’s range of movements and pain in patients with ulnar impaction syndrome. Our results suggest that Darrach’s resection osteotomy may be an effective way to unload the ulnocarpal joint without requiring internal fixation.